Anatomical changes of Akar Putra chicken digestive system after partial ablation of uropygial gland - Jawad, Hasan Saad; Idris, Lokman Hakim; Abu Bakar @ Zakaria, Md Zuki; Kasim, Azhar (Science Publications, 2015)
The current study proposes anatomical changes in the digestive system of 120 Akar Putra chicken after surgical removing of auropygial gland. The experiment comprised of five treatments (24 chicken/treatment), with 3 replicates (8 chicken/replicate). The experimental treatments consist of a control treatment T1; partial ablation of the uropygial gland were applied on T2, T3, T4 and T5 treatments at 3, 4, 5 and 6 weeks of age respectively. The results presents that Partial Uropygialectomy (PU) treatments in males had (p<0.01) longer esophagus 9.9-16.2%, proventriculus 11.1-34.4%, gizzard 26.7-220%, pancreas 0-20.4%, jejunum 4.9-26.1 and colon 18.1-60.6 than the control group counterparts. Furthermore, females of PU treatments had (p<0.01) longer esophagus 6.8-22.3%, pancreas 8.3-33.3% and cecum 13-26% compared with females in control. In contrast, total GIT weight were 21.2 to 78.8% heavier (p<0.01) in males of PU treatments, mainly in the esophagus, duodenum, pancreas, jejunum, ilium and cecum. No significant impact (p>0.05) between treatments was recorded in the total females’ Gastrointestinal Tract (GIT) weight; however, females of PU treatments had 5.9-41.2% heavier ilium (p<0.01) and 11.1-77.8% heavier cecum (p<0.01). Total GIT density, show no significant different (p>0.05) between treatments in females. Nevertheless, it was highly significant different (p<0.01) for males of PU treatments, mainly in esophagus (p<0.05), gizzard (p<0.05), pancreas (p<0.01) and cecum (p<0.05). In conclusion; the results of current study investigated that partial ablation of the uropygial gland had positive effects on the anatomical observations of most digestive system parts.